A trans‐omic Mendelian randomization study of parental lifespan uncovers novel aging biology and therapeutic candidates for chronic diseases. Issue 11 (27th October 2021) - Perrot, Nicolas; Pelletier, William; Bourgault, Jérôme; Couture, Christian; Li, Zhonglin; Mitchell, Patricia L.; Ghodsian, Nooshin; Bossé, Yohan; Thériault, Sébastien; Mathieu, Patrick; Arsenault, Benoit J.
Abstract: The study of parental lifespan has emerged as an innovative tool to advance aging biology and our understanding of the genetic architecture of human longevity and aging‐associated diseases. Here, we leveraged summary statistics of a genome‐wide association study including over one million parental lifespans to identify genetically regulated genes from the Genotype‐Tissue Expression project. Through a combination of multi‐tissue transcriptome‐wide association analyses and genetic colocalization, we identified novel genes that may be associated with parental lifespan. Mendelian randomization (MR) analyses also identified circulating proteins and metabolites causally associated with parental lifespan and chronic diseases offering new drug repositioning opportunities such as those targeting apolipoprotein‐B‐containing lipoproteins. Liver expression of HP, the gene encoding haptoglobin, and plasma haptoglobin levels were causally linked with parental lifespan. Phenome‐wide MR analyses were used to map genetically regulated genes, proteins and metabolites with other human traits as well as the disease‐related phenome in the FinnGen cohorts ( n = 135, 638). Altogether, this study identified new candidate genes, circulating proteins and metabolites that may influence human aging as well as potential therapeutic targets for chronic diseases that warrant further investigation. Abstract : Schematic overview of the analytical framework used to identify novel biological determinants of lifespan and potential drug targets for aging‐associated diseases using genome‐wide association study summary statistics of >1 million parental lifespans.